Public Speaking Strategy for Muslim Lecturers to Attract Generation Z in Da’wah - Rintaningrum, Ratna; Razak, Faisal; Farah, Rina (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The rise of Generation Z as a distinct demographic group has posed new challenges and opportunities for public speaking, especially in the field of da’wah (Islamic preaching). As digital natives, Generation Z engages with content in ways that differ significantly from previous generations, making it essential for Muslim lecturers to adapt their public speaking strategies to connect effectively with this audience. This research explores the public speaking strategies used by Muslim lecturers to attract and engage Generation Z in da’wah. The study employs a qualitative research design, conducting interviews with Muslim lecturers who have successfully used digital platforms and innovative methods to deliver their messages to younger audiences. The findings reveal that interactive content, visual aids, relevant social media usage, and humor are among the most effective strategies for engaging Generation Z. Lecturers who incorporated personal stories and interactive sessions found higher levels of engagement and greater impact. The study concludes that for Muslim lecturers to effectively attract Generation Z, they must embrace modern communication tools while maintaining the integrity and relevance of Islamic teachings. Future research should explore the long-term impact of these strategies and how they affect the retention of Islamic values among Generation Z.